If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 = -4f + 6 + 14 Reorder the terms: 20 = 6 + 14 + -4f Combine like terms: 6 + 14 = 20 20 = 20 + -4f Add '-20' to each side of the equation. 20 + -20 = 20 + -20 + -4f Combine like terms: 20 + -20 = 0 0 = 20 + -20 + -4f Combine like terms: 20 + -20 = 0 0 = 0 + -4f 0 = -4f Solving 0 = -4f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '4f' to each side of the equation. 0 + 4f = -4f + 4f Remove the zero: 4f = -4f + 4f Combine like terms: -4f + 4f = 0 4f = 0 Divide each side by '4'. f = 0 Simplifying f = 0
| 5k-8k=-12 | | -5r-9+4r=-r-9 | | -3t-8+7t=1-4y | | -2(x-5)=40 | | w=90.25(150-n)+115n | | 6f+5=2f-8 | | X^2(x+5)=224 | | 2(2.2+13)=3(5-2.2) | | x^2+32y-2245=0 | | 12y-(11(2-y)-13)=5y+3(7-4y) | | 5-3w=14 | | 14x+45=90 | | 5x^2=109 | | 0.5(x-32)=x | | 34-n=17 | | 3x-2=5y+7 | | 2.4(6y-1.2)=22.8-2.2y | | 24x=3 | | 5(w+6)=7 | | 14x+45= | | -5-x-9=34 | | X+9=18(2x+3)-18 | | -7(2t+10)=-98 | | -3x+y=29 | | 3(f-10)=-48 | | -10(s+5)=-111 | | -0.4170*ln(x-1.0903)=t | | -(c-8)=-2 | | e^2x+3=12 | | 6(t+4)=0 | | -9x+y=85 | | x^2-17x=-10x-3-x^2 |